PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI DINAS PERHUBUNGAN PROVINSI PAPUA BARAT - Andreas Marpaung; Nurlaela Nurlaela; Ted M Suruan (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
Based on the Performance Accountability Report of Government of West Papua Provincial Transport Department in the 2017, there is a decline in the percentage of the performance of civil servants. On the semesters of 2016 amounted to 83,22% to 79,27% in the half of 2017. This shows that for three consecutive semesters there are problems associated with the performance. The research objective is analyze the effect of compensation and career development of the performance of civil servants in the West Papua Provincial Transport Department. The population for the sample of respondents was 40 people by using non probability sampling method. Data analyze techniques used in this research is multiple linear regression. Result of the analysis showed, partially compensated no significant effect (0,870 > 0.05) on the performance of employees, partially significant effect of career development (0.001 < 0,05) on the performance of employees, and simultaneously compensation and career development have significant influence (0,000 < 0.05) on the performance.